Building Secure Elections: E-Voting, Security, and Systems Theory. - Moynihan, Donald P. (Public Administration Review)
The increased use of information technology promises to revolutionize both the provision of government services and the vibrancy of democracy. In the aftermath of the Florida voting controversy during the 2000 presidential election, governments have placed their faith in technology, adopting e-voting machines that offer enhanced voter convenience and eliminate the need for subjective recounts. However, the same underlying assumptions that apply to e-government theory do not apply to e-voting because of the severity of consequences if failure occurs and the loss of transparency traditionally associated with the voting process. A more useful theoretical guide is systems theory, which deals with complex, high-risk systems. This literature has been largely overlooked by adopters of e-voting technology, even though the practical criticisms of e-voting made by computer security specialists reflect an essentially systems theory perspective.